(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2022)
Introduction. The article outlines the need to adapt the strategy of intercultural marketing to the effect of the country of origin of the product or service. The purpose of the work is to analyze the influence of the effect of the origin of goods and services on the consumer behavior of buyers and to identify the practical implications of the formation of an intercultural marketing strategy for companies operating in international markets. The characteristics of cultural aspects of consumer behavior are supplemented by the results of the author’s research on the ranking of the components of the country-of-origin effect. Results. It is noted that intercultural marketing takes into account the need to diversify and adapt marketing activities to the differences arising from different cultures, behavior, preferences and attitudes of buyers. The need for adaptation is the result of different social environment, customs, religion, language, etc. It is established that the country of origin of the goods is a symbol of positive, neutral and negative associations related to this country, which arise in the minds of its inhabitants from other countries or regions. A positive image of a country has a civilizational and economic dimension, as a good reputation is transferred to companies and products. The influence that the image of a given country has on consumers of countries where products from a given country are sold is called the country-of-origin effect. It is substantiated that to determine the effect of the country of origin for tangible and intangible goods in the Roth and Romeo model, it is appropriate to use the following indicators: modernity, diversity, prestige, quality. Conclusions. The results of testing the hypothesis about the multi-vector effect of the country of origin only partially confirm this position. It has been proven that if products and services from a certain country are perceived positively, then this applies to all criteria. The presented calculations showed differences in the assessment of individual indicators of goods and services originating from a certain country. This pattern is inherent in all analyzed countries. It has been proven that the image of Ukrainian products in European countries does not encourage the display of information about their origin. Another problem for Ukrainian enterprises is the loyalty of consumers to foreign products. This obliges enterprises to form a cross-cultural marketing strategy taking into account the effect of the country of origin for the promotion of domestic products on the European and world markets.